Artificial Intelligence for Cyber Defense and Smart Policing - Vijayalakshmi, S. (Associate professor); Durgadevi, P.; Jacob, Lija; Balusamy, Balamurugan; Nand, Parma (Chapman & Hall, 2024)
"The future policing ought to cover the identification of new assaults, the disclosure of new ill-disposed patterns and forecast of any future vindictive patters from the accessible authentic information. Such keen information will bring about building clever advanced proof handling frameworks that will help cops investigate violations. Artificial Intelligence for Cyber Defence and Smart Policing will describe the best way of practising artificial intelligence for cyber defence and smart policing"--